Grup Facebook Bondowoso Bersatu sebagai Ruang Publik Digital: Transformasi Komunikasi Warga dalam Mengawal Kebijakan Infrastruktur - Fuad Nasir (Universitas Majalengka, 2026)
The development of new media has transformed social media into a public communication space where citizens can express aspirations, voice criticism, and monitor government policies. This study aims to analyze how the Bondowoso Bersatu Facebook group functions as a digital communication space for expressing public complaints and criticism regarding infrastructure crises, particularly the collapse of Nangkaan Bridge and the disruption of Koncer Bridge in Bondowoso Regency, Indonesia. This research employed a qualitative approach using netnography by observing posts, comments, photographs, and videos shared within the Facebook group during the infrastructure crisis. The findings reveal that the Facebook group served not only as a platform for public complaints but also evolved into a digital public sphere that facilitated information exchange, public opinion formation, and social control over government policies. Furthermore, citizens' communication patterns transformed from expressing dissatisfaction into collective monitoring through field documentation, online discussions, and evaluation of infrastructure development. These findings highlight the role of local social media communities as digital public communication spaces that foster citizen participation and strengthen government accountability in addressing local public issues